Spatial trends in Gauteng - Ballard, Richard; Mosiane, Ngaka; Hamman, Christian (Gauteng City-Region Observatory, 2021)
As many studies on urban transformation in South Africa have recognised, there is a difference between the ideals of spatial transformation and the ongoing production of space by many kinds of actors who are responding to a wide variety of opportunities and limits. While it might be possible to name post-apartheid urban ideals, unfolding spatial transformations in the democratic era underscore the disbursed nature of the energies producing urban space, and the need to understand and work with these energies as we find them in directing spatial transformation. GCRO's 19th Occasional Paper examines six spatial trends that have shaped Gauteng over the last three decades: Trend 1: From 1990 to 2000, an average of 36 km2 was converted from non-urban land use to urban land use in Gauteng each year. From 2000 to 2010, this decreased to 22 km2 a year, and from 2010 to 2020, it increased slightly to 25 km2 a year. Four-fifths of this growth of urban land cover was in the form of residential land use, most of which was formal. Trend 2: Alongside processes that extend the amount of land being used for urban land use, there is intensifying use of existing urban land. These processes of densification have concentrated half of the province’s residents on just 2% of the province’s land. Trend 3: The number of residential buildings in Gauteng has increased from 2.1 million in 2001 to 3.4 million in 2016. When mapped, new building growth is most prominent in townships where there has been a growth by more than 1 000 new structures per square kilometre in some places. One of the drivers of this growth is the ongoing increase in backyard dwellings. Trend 4: Ongoing production of residential buildings perpetuates, to a large extent, the broad affordability gradient that emerged during the city-region’s segregated history. Using two different types of residential morphology – gated communities and government-provided human settlements – we show that the production of different kinds of residential buildings, catering to divergent income levels, occurs in different parts of the city-region. Trend 5: Although there has been some racial desegregation, particularly in residential areas once set aside for white people, the city-region continues to show socio-economic segregation. An analysis of segregation shows the way in which middle-class suburbs are racially integrated but not diversified by income. Meanwhile, the more affordable nature of accommodation in townships continues to restrict working class populations to such spaces. Trend 6: The location of commercial and industrial buildings suggests an ongoing disjuncture between the largest residential population concentrations and many economic zones. This ‘spatial mismatch’ creates the need for people to commute long distances every day to work or to look for work. However, commercial and industrial buildings are also developing in and near townships.
Keywords: spatial trends, Gauteng, urban sprawl, densification, building growth, segregation, mismatch